2021
DOI: 10.1016/j.pedneo.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Psychological correlates of eating behavior in overweight/obese adolescents in Taiwan: Psychometric and correlation analysis of the Three-Factor Eating Questionnaire (TFEQ)-R21

Abstract: Pediatrics and Neonatology xxx (xxxx) xxx three pre-conceptualized domains in the data. Further univariate and multivariate linear regression analyses were applied to identify the correlates of different TFEQ-R21 subdomains. Results: The Comparative Fit Index for the TFEQ-R21 was 0.908, which confirmed the threefactor structure (i.e., cognitive restraint [CR], uncontrolled eating [UE], and emotional eating [EE]) in the Taiwan version of TFEQ-R21. Only CR correlated with disordered eating (r Z 0.351, p < 0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
2
23
0
1
Order By: Relevance
“…Table 18 shows the correlation analysis for sports health, self-efficacy, and sports. Correlation analysis [ 27 ] is performed in the questionnaire work for sports health, self-efficacy, and sports commitment. The correlation analysis of sports health and self-efficacy and sports commitment shows a significant correlation between youth sports health and sports commitment, significant activity level P < 0.05, and Pearson correlation coefficients are 0.856, 0.815, and 0.662, respectively, indicating a significant positive correlation between sports health and self-efficacy and sports commitment, self-efficacy, and sports commitment.…”
Section: Resultsmentioning
confidence: 99%
“…Table 18 shows the correlation analysis for sports health, self-efficacy, and sports. Correlation analysis [ 27 ] is performed in the questionnaire work for sports health, self-efficacy, and sports commitment. The correlation analysis of sports health and self-efficacy and sports commitment shows a significant correlation between youth sports health and sports commitment, significant activity level P < 0.05, and Pearson correlation coefficients are 0.856, 0.815, and 0.662, respectively, indicating a significant positive correlation between sports health and self-efficacy and sports commitment, self-efficacy, and sports commitment.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies on disordered eating among Taiwanese adolescents have revealed higher body dissatisfaction rates among girls than boys [ 32 , 33 ]. In Taiwan, a survey of junior high school participants discovered that anxiety and weight-related self-stigmatization were strongly associated with emotional eating among girls.…”
Section: Introductionmentioning
confidence: 99%
“…A correlation seems to exist between physical activity and restrained eating. The results of a previous study indicated that girls at high risk of developing an eating disorder, performed more physical activity, with the goal of losing weight [ 12 ]. Indeed, more eating restriction was observed in adolescents who practiced more physical activity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social factors include family, parents and media. A previous study demonstrated that teasing by family and friends, as well as internalized weight stigma, especially that related to weight and body shame and guilt, are correlated with eating disorder [ 12 ]. Parents, family and media can lead the individual to restrained eating by influencing him/her to reach the “perfect weight” [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%